2020
DOI: 10.1007/s00167-020-05865-1
|View full text |Cite
|
Sign up to set email alerts
|

Excellent mid-term osseointegration and implant survival using metaphyseal sleeves in revision total knee arthroplasty

Abstract: Purpose Metaphyseal fixation in revision total knee arthroplasty (RTKA) is a very promising treatment option for extended bone defects. Currently published mid-term results remain limited. The purpose was to analyse the implant durability, the clinical and the radiological mid-term results in RTKA when using metaphyseal sleeves. Methods Clinical and radiological follow-up examinations were performed in 92 patients (93 knees) with RTKA using hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…It also shows signi cant improvement in patients' postoperative joint functions and knees ROM. Klim et al [20] conducted a 6.3-year follow-up of 93 RTKA with bone defects restored with metaphyseal sleeves. Not even a single case shows aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows signi cant improvement in patients' postoperative joint functions and knees ROM. Klim et al [20] conducted a 6.3-year follow-up of 93 RTKA with bone defects restored with metaphyseal sleeves. Not even a single case shows aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown successful outcomes of MS in RKA with significant improvement in functional scores and excellent rate of osseointegration [ 26 28 ]. Implant survival rates of 94% to 100% have been reported at the midterm follow-up, with the endpoint being aseptic loosening [ 29 , 30 ]. Bloch et al recently reported a large series of 227 patients (319 RKA) using the MS (319 tibial and 146 femoral) with a mean follow-up of 7.6 years [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another recent study by Kim et al which included 92 patients (93 RKA) with a mean follow-up of 6.3 years also demonstrated satisfactory results. The authors reported average improvements of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) from 55 preoperatively to 9 postoperatively and the Subjective Satisfaction Score (SSS) from 2 preoperatively to 8 postoperatively (both p < 0.05) [ 29 ]. All patients in their series demonstrated optimal osseointegration at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…If the bone defect is primarily manifested as substantial cavitary loss of cancellous bone at the metaphysis and the surrounding cortical bone is relatively intact, then augmentation, either in block or wedge, is not recommended for defect reconstruction ( 60 ). Instead, metaphyseal sleeves and cones are ideal alternatives to ensure a preferable clinical outcome ( 61 , 62 ). Generally, the geometry and appearance of sleeves and cones are analogical, but they have different design concepts and surgical techniques ( Fig.…”
Section: Design and Rationale Of Prostheses In Rtkamentioning
confidence: 99%